Leadership Over-Emergence in Self-Managing Teams: The Role of Gender and Countervailing Biases - Lanaj, Klodiana; Hollenbeck, John R. (Academy of Management Journal, 2015)
We examine leadership over-emergence, defined as instances when the level of one’s leadership emergence is higher than the level of one’s leadership effectiveness, in a sample of intact self-managing teams who worked together for a period of seven months. We draw from Gender Role Theory and Expectancy Violation Theory to examine the role of gender in predicting leadership over-emergence. Building on arguments from Gender Role Theory, we find that all else equal, men over-emerge as leaders. However, Expectancy Violation Theory suggests that women are likely to benefit from a countervailing bias. Specifically, women are attributed with higher levels of leadership emergence than men when they engage in agentic leadership behaviors—even if the level of the behaviors exhibited by men is exactly the same. Because the impact of these behaviors on leadership effectiveness is not contingent on gender, however, women who engage in more task behaviors and boundary spanning behaviors in self-managing teams also over-emerge as leaders. We discuss the implications of this study for Gender Role Theory and Expectancy Violation Theory, along with practical implications for managing the problem of leadership over-emergence in work groups.